Water Resources Assessment in Shukhi Station - Reshteen, Sediqullah (Journal of Natural Sciences – Kabul University, 2025)
Since the beginning of human life, water resources have been central to the formation of residential communities, whether in large cities or small villages. Although Afghanistan is located in the desert region of Central Asia, it still has a number of permanent rivers. All rivers in Afghanistan, except for the Kabul River, either flow into lakes or are absorbed in the desert. The rivers in Afghanistan generally have a seasonal regime, with most of their flow coming from direct rainfall and snowmelt from permanent glaciers. This process ensures that the rivers have water throughout the year.